Cytokines and Chemokines at the Crossroads of Neuroinflammation, Neurodegeneration, and Neuropathic Pain - Geeta Ramesh; Andrew G. MacLean; Mario T. Philipp (Mediators of Inflammation)
Cytokines and chemokines are proteins that coordinate the immune response throughout the body. The dysregulation of cytokines and chemokines is a central feature in the development of neuroinflammation, neurodegeneration, and demyelination both in the central and peripheral nervous systems and in conditions of neuropathic pain. Pathological states within the nervous system can lead to activation of microglia. The latter may mediate neuronal and glial cell injury and death through production of proinflammatory factors such as cytokines and chemokines. These then help to mobilize the adaptive immune response. Although inflammation may induce beneficial effects such as pathogen clearance and phagocytosis of apoptotic cells, uncontrolled inflammation can result in detrimental outcomes via the production of neurotoxic factors that exacerbate neurodegenerative pathology. In states of prolonged inflammation, continual activation and recruitment of effector cells can establish a feedback loop that perpetuates inflammation and ultimately results in neuronal injury. A critical balance between repair and proinflammatory factors determines the outcome of a neurodegenerative process. This review will focus on how cytokines and chemokines affect neuroinflammation and disease pathogenesis in bacterial meningitis and brain abscesses, Lyme neuroborreliosis, human immunodeficiency virus encephalitis, and neuropathic pain.